Interaktioner mellan människa och tamkatt (Felis silvestris catus) - Pålsson, Olivia (2020)
Throughout the history of mankind, our intertwined story with the domestic cat (Felis silvestris catus) is a complex one. From being a tiny solitary hunter who lived among humans and their unwanted debris, until today when the cat is one of the most popular pets in the world. Therefore, the human-cat interactions are countless and can be positive or negative which of course can engender varying effects for both humans and cats. Also, the environment in which the interactions takes place seems to alter as well. For this reason, this paper aimed to identify the different interactions between humans and cats, in which environments the interactions occur and what factors are affecting them. Also, what positive and negative effects can be seen among cats and humans were investigated. The methodology that was used in this thesis was a literature review. The information was collected from different articles, books and scientific studies from Primo (SLU-university library search engine), Web of Science, PubMed, Scopus and Google Scholar. The results indicate that the environments in which the positive and negative interactions occur are many, from cat cafés to the home environment, and these environments seem to influence the interactions. However, research processing the effects of the human-cat interactions is uncertain due to both positive and negative results around health benefits, stress, social needs and support. Factors affecting the interactions between cats and humans are for instance the experience of people, age and gender. To conclude, more research is needed to gain a more complete and holistic understanding of human-cat interactions and the factors affecting them.